The Impact of Human Development Quality on Poverty: Evidence from Panel Data of South Sulawesi Province - Ibnoe Ramadhani; Prima Agung Palupi (Faculty of Economics and Bussiness, Universitas Diponegoro, Semarang, Indonesia, 2025)
The eradication of poverty is a critical priority for both central and local governments. Human development plays a vital role in lifting communities out of poverty. This study examines how the quality of human development affects poverty across 24 districts/cities of South Sulawesi over 2012–2022, using the Generalized Method of Moments (GMM). Life expectancy, as a proxy for health quality, has no significant effect on poverty reduction, whereas primary and secondary school enrolment rates show a significant negative effect. Government spending on education and health also reduces poverty significantly, while the open unemployment rate and the COVID-19 dummy are associated with higher poverty. Per capita expenditure and access to clean water show no significant effect. The study contributes district-level evidence on poverty, using a dynamic panel approach that accounts for the persistence of poverty over time and corrects for endogeneity. Its originality lies in addressing the gap between the province's rising human development index and a poverty level that has not declined alongside it, which gives local government a more targeted basis for policy.